In vitro cytotoxicity and anthocyanin studies on Pithecellobium Dulce (ROXB.) Benth (Fruits) against mcf 7 cell lines - A.SUGANTHI,; R. MARY JOSEPHINE, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the study was to find out the anthocyanin and anticancer efficacy of Pithecellobium dulce (Roxb.) Benth fruits extract against MCF -7 (Michigdan Cancer Foundation-7).Different concentration (10, 20, 30, 40, and 50 μg/ml) of methanol extract of P.dulce fruits were used to assess the in vitro cytotoxic effect using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Pithecellobium dulce fruits contain 6.23 % of anthocyanin. The various concentrations of crude methanol extract (10, 20, 30, 40, and 50 μg/ml concentration) of Pithecellobium dulce fruits were performed for cytotoxic activity. The effect of inhibition of cell growth showed significantly cytotoxic against MCF-7 cell line with an inhibit cell growth by 50% (IC50) of 24μg/ml.The present study concludes that the methanol extract of Pithecellobium dulce fruits possess potent cytotoxic activity.